Emergence and transmission of Carbapenem-resistant Enterobacteriaceae blaNDM-5 gene in healthy pigs in Baise, Guangxi, China: a discovery - Dai, Yuan-Yuan; Wei, Wen-Fei; Li, Xue-zhen; Yuan, Chao-Yuan; Zhao, Li-Juan; Huang, Yan-Qiang; Hao, Ming; Deng, Ying; Teng, Yuan-Ji; Yi, Xue-Li (Frontiers in Veterinary Science, 2025)
A total of 366 tonsillar tissue samples were collected from healthy free-range pigs owned by farmers across 12 districts in Baise City, Guangxi, China. This initiative successfully isolated six strains of Carbapenem-Resistant Enterobacteriaceae (CRE), including four strains of Escherichia coli, and one of Klebsiella aerogenes and Morganella morganii. Assessments utilizing Carbapenemase inhibitor enhancement test, in conjunction with the ResFinder resistance gene database, revealed that five strains carried the blaNDM-5 gene, while one strain possessed the blaNDM-1 gene. The overall positivity rate for CRE was determined to be 1.64%. Conjugation tests further demonstrated the ability of the blaNDM genes to transfer to recipient strains. Additionally, an analysis of the genetic environment surrounding the blaNDM genes showed similarities among the genes within the same geographic region, suggesting that these strains may have originated from a common ancestor and spread horizontally among different clones. This study provides valuable insights into the transmission of CRE among free-range farmers in Baise City, Guangxi, China.